Utilization Of Information Through Communication Media On The Behavior Of Farmers (Case Of Vegetable Farmers In Casket Hillion, Wayame Village, Ambon City) - Amelia Puttileihalat; Risyart. A. Far Far; Paul Melkianus Puttileihalat (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyze the relationship between the use of communication media and changes in the behavior of vegetable farmers. This research was conducted in Basket Hamlet, Wayame Village, Ambon City. Quantitative research approach, saturated sampling in designating a sample of 25 farmers. Data analysis uses Rank Spearman to see the relationship between variables. The research results show thatthere is no significant relationship between the content of information on vegetable cultivation via radio and TV and changes in farmer behavior. Meanwhile, leaflets and brochures have a real relationship between the content of information on vegetable cultivation and farmer behavior.